Comparison of wavelength propagation for free space optical communications - Naimullah, B. S S; Mohamad, Othman; Rahman, A. K.; Suzana, I. Sulaiman; Ishak, S.; Salasiah, Hitam; Syed Alwee Aljunid, Syed Junid (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org